Bagian Ayah Seperenam dan Seluruh Harta Warisan; Analisis dari Nas?s? Al-Qur’an - Syuhada' Syuhada' (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2015)
The nature of the text al-Kitâb and al-Sunnah of the provisions of inheritance is very limited and globally thus allowing the door of ijtihâd. Limited and global conditions said can be tolerated as long as does not violate the basic provisions of the Al-Qur’an itself. Results ijtihâd against inheritance verses of the Al-Qur’an in Indonesia partly contained in the compilation of Islamic law which was appointed by the Minister of Religion and the Presidential Instruction as a guide for religious court and Indonesia’s Islamic society in resolving the dispute case in the field of marriage law, inheritance and waqf. Article 177 of Book II of the Inheritance Law KHI those who called for the third part of the father although impressed hold because parts of it are not referred to by the verses of the Koran, but it does not make any mention of a new law which is different from the law of the Al-Qur’an. Based on the adage that an object must be an owner, the transfer of property to heirs who are still living with the media khalafiyah (forwarding ownership) in the case of Article 177 remain to be resolved by the law of the Al-Qur’an.